Deradikalisasi Pluralisme Pemahaman terhadap Ideologi Pancasila Melalui Media Sosial - Arifin, Zainal; Handayani, Emi Puasa; Virdaus, Saivol (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to analyze the challenges and threats to the Pancasila ideology and analyze deradicalization efforts to eliminate pluralism in understanding the Pancasila ideology through social media. This study used a qualitative method with a philosophical, historical, and conceptual approach. The study results showed that the Pancasila ideology faced several challenges and threats, including the influence of significant world ideologies, including socialism, liberalism, and communism, and the existence of radicalism, which was growing now. Educators could help deradicalization through social media by aligning students' understanding that Pancasila was extracted from existing, materialized, and inherent culture or habits in the Indonesian nation. In addition, exceptional training and guidance for a citizen journalist need to be carried out to deradicalize.